FAKTOR DETERMINAN DEVIDEND PAYOUT RATIO BANK UMUM SYARIAH PADA BURSA EFEK INDONESIA - Muksal, Muksal; Gultom, Muhammad Aidil (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Dividend payout ratio (DPR) is usually determined by management by considering several factors of the company's financial performance through several ratios finance. Among these financial ratios is Return On Assets (ROA), firm size, and growth opportunity. The aim of this research is to analyze the influence of ROA, firm size and growth opportunity on DPR (dividend payout ratio) in Sharia Commercial Banks listed on the Indonesia Stock Exchange Period 2014-2021. The research subjects were 4 Sharia Commercial Banks, with a range of observation year 2014-2021, so the number of observation subjects is 20 observation. The type of data that the author uses in writing this thesis is data secondary, namely the company's annual financial report data obtained from the official website of the Indonesian Stock Exchange www.idx.co.id, and then analyze quantitatively with multiple linear regression using the SPSS application. The research results found the influence of (ROA), Firm Size and Growth Opportunities jointly or simultaneously influence DPR at Sharia Commercial Banks listed on the IDX for the 2014-2021 period, both simultaneously and simultaneously Partial. Investors should first consider the variables affects the DPR,because this aspect measures the company's ability to generate a good level of return on investment carried out at the company.Dividend Payout Ratio (DPR) biasanya ditentukan oleh pihak manajemen dengan mempertimbangkan beberapa faktor-faktor kinerja keuangan perusahaan melalui beberapa rasio-rasio keuangan. Di antara rasio keuangan tersebut adalah Return On Asset (ROA), firm size, dan growth opportunity. Tujuan penelitian ini untuk untuk menganalisis pengaruh ROA, firm size dan growth opportunity terhadap DPR (dividend payout ratio) pada Bank Umum Syari'ah yang terdaftar di Bursa Efek Indonesia Periode 2014-2021. Subjek penelitian adalah 4 Bank Umum Syariah, dengan rentang tahun pengamatan 2014-2021, sehingga jumlah subjek observasi adalah 20 pengamatan. Jenis data yang penulis gunakan dalam penulisan skripsi ini data sekunder, yaitu data laporan keuangan tahunan perusahaan yang diperoleh dari website resmi Bursa Efek Indonesia www.idx.co.id, dan kemudian dianalisis secara kuantitatif dengan regresi linier berganda menggunakan aplikasi SPSS. Hasil penelitian menemukan adanya pengaruh Return On Asset (ROA), Firm Size dan Growth Oppotunity secara bersama-sama atau simultan berpengaruh terhadap Dividen Payout Ratio pada Bank Umum Syariah yang terdaftar di Bursa Efek Indonesia periode tahun 2014-2021, baik itu secara simultan maupun secara parsial. Investor hendaknya terlebih dahulu mempertimbangkan variabel yang mempengaruhi Dividend Payout Ratio (DPR), karena aspek ini mengukur kemampuan perusahaan dalam menghasilkan tingkat laba atas investasi yang dilakukan pada perusahaan tersebut.Dividend payout ratio (DPR) is usually determined by management by considering several factors of the company's financial performance through several ratios finance. Among these financial ratios is Return On Assets (ROA), firm size, and growth opportunity. The aim of this research is to analyze the influence of ROA, firm size and growth opportunity on DPR (dividend payout ratio) in Sharia Commercial Banks listed on the Indonesia Stock Exchange Period 2014-2021. The research subjects were 4 Sharia Commercial Banks, with a range of observation year 2014-2021, so the number of observation subjects is 20 observation. The type of data that the author uses in writing this thesis is data secondary, namely the company's annual financial report data obtained from the official website of the Indonesian Stock Exchange www.idx.co.id, and then analyze quantitatively with multiple linear regression using the SPSS application. The research results found the influence of (ROA), Firm Size and Growth Opportunities jointly or simultaneously influence DPR at Sharia Commercial Banks listed on the IDX for the 2014-2021 period, both simultaneously and simultaneously Partial. Investors should first consider the variables affects the DPR,because this aspect measures the company's ability to generate a good level of return on investment carried out at the company.